Complement Receptor 1 (CR1, CD35) Polymorphisms and Soluble CR1: A Proposed Anti-inflammatory Role to Quench the Fire of “Fogo Selvagem” Pemphigus Foliaceus - Oliveira, Luana Caroline; Kretzschmar, Gabriela Canalli; dos Santos, Andressa Cristina Moraes; Camargo, Carolina Maciel; Nisihara, Renato Mitsunori; Farias, Ticiana Della Justina; Franke, Andre; Wittig, Michael; Schmidt, Enno; Busch, Hauke; Petzl-Erler, Maria Luiza; Boldt, Angelica Beate Winter (Frontiers in Immunology, 2019)
Pemphigus foliaceus is an autoimmune disease, sporadic around the world but endemic in Brazil, where it is known as fogo selvagem (FS). Characterized by autoantibodies against the desmosomal cadherin desmoglein 1, FS causes painful erosions and crusts that may be widespread. The recognition of antigens, including exposed sugar moieties, activates the complement system. Complement receptor 1 (CR1/ CD35), responsible for the Knops blood group on erythrocytes (York and McCoy antigens), is also expressed by antigen-presenting cells. It regulates the complement system by removing opsonized antigens, blocking the final steps of the complement cascade. Membrane-bound CR1 also fosters antigen presentation to B cells, whereas soluble CR1 has anti-inflammatory properties. CR1 gene polymorphisms have been associated with the susceptibility to complex diseases. In order to investigate their association with FS susceptibility, we developed a multiplex sequence-specific assay to haplotype eleven polymorphisms in up to 367 FS patients and 242 controls from an endemic area, and 289 from a non-endemic area. We also measured soluble CR1 (sCR1) in serum of 53 FS patients and 27 controls, and mRNA levels in peripheral blood mononuclear cells of 63 genotyped controls. The haplotypes CR1*3B2B (with the York antigen – encoded by p.1408Met) and CR1*3A2A (with p.1208Arg) were associated with protection against FS (OR=0.57, P=0.027 and OR=0.46, P=0.014, respectively). In contrast, the CR1*1 haplotype (with the McCoy antigen – encoded by p.1590Glu) was associated with FS susceptibility (OR=4.97, P<0.001). Heterozygote rs12034383*A/G presented higher mRNA expression than homozygotes with the G allele (P=0.04). Lowest sCR1 levels occurred in patients with active disease, before treatment (P=0.036). Patients in remission had higher levels of sCR1, compared to healthy controls (P=0.013). Among those under treatment, patients with localized lesions also presented higher sCR1 levels, than those with generalized lesions (P=0.0073). In conclusion, the Knops blood group seems to modulate susceptibility to the disease. Furthermore, corticosteroid treatment might increase sCR1 serum levels and higher levels may play an anti-inflammatory role in patients with FS, limiting the distribution of lesions. Based on these results, we suggest CR1 as a potential new therapeutic target for the treatment of FS.